Assessment of knowledge, attitudes, and practices regarding menstruation and menstrual hygiene among early-reproductive aged women in Bangladesh: a cross-sectional survey - Siddique, Abu Bakkar; Deb Nath, Sudipto; Mubarak, Mahfuza; Akter, Amena; Mehrin, Sanjida; Hkatun, Mst Jemi; Parvine Liza, Antara; Amin, M. Ziaul (Frontiers in Public Health, 2023)
Background: Poor menstrual hygiene practices during menstruation increases the risk of reproductive tract infections, absenteeism, and negative impact on school performance. Despite being a global problem, there is a lack of knowledge and misconceptions about menstrual hygiene among women of all ages, especially in developing countries like Bangladesh. The study aims to assess the knowledge, attitudes, and practices towards menstrual hygiene among early reproductive-aged women in Bangladesh to help policymakers and planners take effective initiatives.A cross-sectional survey was conducted between July and December 2022 in Dhaka, Rajshahi, Chittagong, Sylhet, and Barisal regions of Bangladesh. A convenience sampling technique was utilized to recruit a total of 1,214 participants (100% female; mean age: 22.87 ± 2.64 years). A semi-structured questionnaire including informed consent, socio-demographic information, as well as questions regarding knowledge (6-item), attitudes (7-item), and practices (6-item) towards menstruation and menstrual hygiene practices, was used to conduct the survey.All analyses were performed using the STATA (Version 15.0) and Statistical Package for the Social Sciences (SPSS version 25.0).The mean scores of the knowledge, attitudes, and practices were 4.9 ± 1.51 (out of 6), 12.58 ± 1.58 (out of 14), and 8.80 ±1.87 (out of 12), respectively. The higher scores of knowledge, attitudes, and practices were significantly associated with several socio-demographic and menstruation-related factors (education, family type, type of menstruation, duration of menstruation, etc.).This study identified several key factors associated with improved knowledge, attitudes, and practices related to menstrual hygiene, including higher education levels, student status, younger age, non-alcohol consumption, and regular menstrual cycles. To enhance menstrual hygiene practices among women, it is crucial to implement targeted interventions that address knowledge disparities and tackle social and environmental influences.